Myocarditis and neutrophil-mediated vascular leakage but not cytokine storm associated with fatal murine leptospirosisResearch in context - Stylianos Papadopoulos; David Hardy; Frédérique Vernel-Pauillac; Magali Tichit; Ivo G. Boneca; Catherine Werts (EBioMedicine)
Summary: Background: Leptospirosis is a globally neglected re-emerging zoonosis affecting all mammals, albeit with variable outcomes. Humans are susceptible to leptospirosis; infection with Leptospira interrogans species can cause severe disease in humans, with multi-organ failure, mainly affecting kidney, lung and liver function, leading to death in 10% of cases. Mice and rats are more resistant to acute disease and can carry leptospires asymptomatically in the kidneys and act as reservoirs, shedding leptospires into the environment. The incidence of leptospirosis is higher in tropical countries, and countries with poor sanitation, where heavy rainfall and flooding favour infection. Diagnosis of leptospirosis is difficult because of the many different serovars and the variety of clinical symptoms that can be confused with viral infections. The physiopathology is poorly understood, and leptospirosis is often regarded as an inflammatory disease, like sepsis. Methods: To investigate the causes of death in lethal leptospirosis, we compared intraperitoneal infection of male and female C57BL6/J mice with 108 Leptospira of two strains of pathogenic L. interrogans. One strain, L. interrogans Manilae L495, killed the mice 4 days after infection, whereas the other strain, L. interrogans Icterohaemorrhagiae Verdun, did not induce any major symptoms in the mice. On day 3 post infection, the mice were humanely euthanised and blood and organs were collected. Bacterial load, biochemical parameters, cytokine production and leucocyte population were assessed by qPCR, ELISA, cytometry and immunohistochemistry. Findings: Neither lung, liver, pancreas or kidney damage nor massive necroptosis or cytokine storm could explain the lethality. Although we did not find pro-inflammatory cytokines, we did find elevated levels of the anti-inflammatory cytokine IL-10 and the chemokine RANTES in the serum and organs of Leptospira-infected mice. In contrast, severe leptospirosis was associated with neutrophilia and vascular permeability, unexpectedly due to neutrophils and not only due to Leptospira infection. Strikingly, the main cause of death was myocarditis, an overlooked complication of human leptospirosis. Interpretation: Despite clinical similarities between bacterial sepsis and leptospirosis, striking differences were observed, in particular a lack of cytokine storm in acute leptospirosis. The fact that IL-10 was increased in infected mice may explain the lack of pro-inflammatory cytokines, emphasising the covert nature of Leptospira infections.Neutrophilia is a hallmark of human leptospirosis. Our findings confirm the ineffective control of infection by neutrophils and highlight their deleterious role in vascular permeability, previously only attributed to the ability of leptospires to damage and cross endothelial junctions.Finally, the identification of death due to myocarditis rather than kidney, liver or liver failure may reflect an overlooked but common symptom associated with poor prognosis in human leptospirosis.These features of neutrophilia and myocarditis are also seen in patients, making this mouse model a paradigm for better understanding human leptospirosis and designing new therapeutic strategies. Funding: The Boneca laboratory was supported by the following programmes: Investissement d’Avenir program, Laboratoire d’Excellence “Integrative Biology of Emerging Infectious Diseases” (ANR-10-LABX-62-IBEID) and by R&D grants from Danone and MEIJI. CW received an ICRAD/ANR grant (S-CR23012-ANR 22 ICRD 0004 01). SP received a scholarship by Université Paris Cité (formerly Université Paris V – Descartes) through Doctoral School BioSPC (ED562, BioSPC). SP has additionally received a scholarship “Fin de Thèse de Science” number FDT202404018322 granted by “Fondation pour la Recherche Médicale (FRM)”. The funders had no implication in the design, analysis and reporting of the study.